Characterisation of an ischemia reperfusion model for the formation of a stage I pressure ulcer in mouse skin. Issue 3 (August 2021) - Kwek, Milton Sheng Yi; Thangaveloo, Moogaambikai; Hui, Sophia Lim Beng; Madden, Leigh E.; Phillips, Anthony RJ.; Becker, David L.
Abstract: Pairs of magnets were applied to the loose skin on the backs of mice in order to cause ischemia for periods of 1.5, 2, 2.5 and 3 h followed by reperfusion. We found 1.5 h of ischemia resulted in the most reliable outcome of blanched skin but no redness or skin breakdown. Histological analysis at 4 h of reperfusion showed, in the centre of the insult, condensed nuclei in the epidermis and sebaceous glands with a build up of neutrophils in the blood vessels, and a reduction in the number of fibroblasts. At 24 h, spongiosis was seen in the epidermis and pockets of neutrophils began to accumulate under it, as well as being scatted through the dermis. In the centre of the insult there was a loss of sebaceous gland nuclei and fibroblasts. Four days after the insult, spongiosis was reduced in the epidermis at the edge of the insult but enhanced in the centre and in hair follicles. Leukocytes were seen throughout the central dermis. At 8 days, spongiosis and epidermal thickness had reduced and fibroblasts were reappearing. However, blood vessels still had leukocytes lining the lumen. The gap junction protein connexin 43 was significantly elevated in the epidermis at 4 h and 24 h reperfusion. Ischemia of 1.5 h generates a sterile inflammatory reaction causing the loss of some cell types but leaving the epidermis intact reminiscent of a stage I pressure ulcer. Graphical abstract: Image 1 Highlights: Ischemia reperfusion injury in skin leads to sterile inflammation. Blood vessels become leaky and there is a build up of neutrophils in the dermis. Spongiosis is seen in the epidermis. Fibroblasts are lost from the centre of the insult. Inflammation resolves and fibroblasts return.